1994
DOI: 10.1093/tropej/40.2.78
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Mortality at the Ogun State University Teaching Hospital, Sagamu, Nigeria

Abstract: A study of perinatal mortality at the Ogun State University Teaching Hospital during the first 30 months (March 1989 to August, 1991) of the establishment of a separate neonatal unit was made. One-hundred-and-sixty-two (87.5/1000) of the 1852 deliveries were stillborn and 60 (35.5/1000) of the 1690 live births died in the early neonatal period. The overall perinatal mortality rate was 119.9/1000 deliveries. Of stillbirths, 82 per cent occurred in unbooked mothers and were diagnosed at presentation. The major c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
38
2

Year Published

1996
1996
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 0 publications
7
38
2
Order By: Relevance
“…This was reflected in the fact that majority of the stillbirths 84% occurred in the unbooked patients. This is also similar to findings in Shagamu[14] and Lagos,[16] Nigeria, which showed that majority of the women were unbooked. Being unbooked, these women cannot fully access antenatal care, which includes the detection of at risk women and providing them with specialized care and delivery.…”
Section: Discussionsupporting
confidence: 90%
“…This was reflected in the fact that majority of the stillbirths 84% occurred in the unbooked patients. This is also similar to findings in Shagamu[14] and Lagos,[16] Nigeria, which showed that majority of the women were unbooked. Being unbooked, these women cannot fully access antenatal care, which includes the detection of at risk women and providing them with specialized care and delivery.…”
Section: Discussionsupporting
confidence: 90%
“…This finding was similar to that in Orlu and shagamu [2] [25]. Being unbooked, these women cannot fully access antenatal care, which includes the detection of women at risk and providing them with specialized care and delivery [26].…”
Section: O D Okochi Et Alsupporting
confidence: 69%
“…8 It is difficult to generalize on facility and community based rates as neonatal mortality in facility deliveries as low as 16.4 per 1000 live births and as high as 51 per 1000 live births were obtained in similar Nigerian communities at the time of the study. 15,16 What may explain the relatively lower rates obtained in this study could be the presence of the Department of Community Medicine, Public Health Clinic which provided preventive education and care to the community for many years (excluding obstetric care). The verification exercise done after the reported vital event gives one the assurance that very few births and deaths were missed.…”
Section: Discussionmentioning
confidence: 73%